May Measurement Month 2017: an analysis of blood pressure screening results from the United Arab Emirates—Northern Africa and Middle East. (24th April 2019) - Yusufali, Afzalhussein; Bazargani, Nooshin; Agrawal, Amrish; Muhammed, Khalifa; Obaid, Hanan; Gabroun, Ahmed; Albadwawi, Mouza; Albawab, Amer; Musa, Anas; Alraeesi, Fatima; Vazir, Zainab; Varghese, Rekha; et al.
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programmes worldwide. United Arab Emirates has a young population, but cardiovascular disease (CVD) is the commonest cause of death (40%). Myocardial infarction and stroke occurs at least a decade earlier than in western countries. Previous screening in our young population showed that 85% of the population had at least one CVD risk factor and about 62% of them were unaware of it. An opportunistic cross-sectional survey of volunteers aged ≥18 was carried out in May 2017. Blood pressure measurement, the definition of hypertension and statistical analysis followed the standard MMM protocol. Screening was held in 23 sites such as mosques, sports, and men's/ladies' clubs, airports, parks, shopping malls, work places as well as their residences, and in the public areas of hospitals or outpatient clinics. A total of 6193 individuals were screened during MMM17. The mean age was 39.2 ± 13.1 years. After multiple imputation, 1867 (30.2%) had hypertension. Of individuals not receiving anti-hypertensive medication, 813 (15.8%) were hypertensive. Of 1054 individuals receiving anti-hypertensive medication, 427 (40.6%) had uncontrolled BP. MMM17 was a useful screening model as it makes BP measurement easily accessible. Eight hundred and thirteen (16%) possibly new hypertensives were uncovered and 427(40.6%) of those on treatment for hypertension were found to be uncontrolled. These results suggest that opportunistic screening can identify significant numbers with raised BP.